2016
DOI: 10.1158/0008-5472.can-15-2596
|View full text |Cite
|
Sign up to set email alerts
|

Guidance Molecule SEMA3A Restricts Tumor Growth by Differentially Regulating the Proliferation of Tumor-Associated Macrophages

Abstract: Accumulation of tumor-associated macrophages (TAM) correlates with malignant progression, immune suppression, and poor prognosis. In this study, we defined a critical role for the cellsurface guidance molecule SEMA3A in differential proliferative control of TAMs. Tumor cell-derived SEMA3A restricted the proliferation of protumoral M2 macrophages but increased the proliferation of antitumoral M1, acting through the SEMA3A receptor neuropilin 1. Expansion of M1 macrophages in vivo enhanced the recruitment and ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 40 publications
3
59
1
Order By: Relevance
“…Furthermore, in response to the HFD, Nrp1 myel-KO mice displayed impaired glucose homeostasis and blunted insulin sensitivity relative to WT mice. Unlike previous studies that majorly showed the involvement of macrophage Nrp1 in the regulation of tumor growth (19,20), our current study demonstrates the causative role of macrophage Nrp1 in HFD-induced insulin resistance. Our results are in line with other reports in which Sema3 family members and their cognate receptors have been linked to insulin resistance.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, in response to the HFD, Nrp1 myel-KO mice displayed impaired glucose homeostasis and blunted insulin sensitivity relative to WT mice. Unlike previous studies that majorly showed the involvement of macrophage Nrp1 in the regulation of tumor growth (19,20), our current study demonstrates the causative role of macrophage Nrp1 in HFD-induced insulin resistance. Our results are in line with other reports in which Sema3 family members and their cognate receptors have been linked to insulin resistance.…”
Section: Discussioncontrasting
confidence: 89%
“…Consistently, Miyauchi et al (19) reported that Nrp1 ablation in glioma-associated microglia and macrophages suppresses glioma progression by promoting M1 macrophage polarization. Recent findings further establish the involvement of the Sema3A/Nrp1 axis, as well as M1/M2 macrophages, with respect to tumorigenic processes (20). However, specific functions of macrophage Nrp1 in the context of metabolic dysfunction, such as obesity-associated insulin resistance, have not been investigated.…”
Section: Introductionmentioning
confidence: 70%
“…One study reported that SEMA3A regulates phosphorylation of phosphatase and tensin homolog, which in turn activates a chain of TSGs to inhibit breast cancer growth, invasiveness and angiogenic capacity . Another study demonstrated a role for SEMA3A in proliferative control of tumor‐associated macrophages . Silencing of SEMA3A in many types of cancer, including breast cancer, was found in publicly available gene expression data in clinical samples, which further supports a tumor suppressor role of SEMA3A ( Figure A).…”
Section: Resultsmentioning
confidence: 56%
“…Among genes that were the most robustly hypomethylated in invasive MCF10CA1a cells, we observed a progressive RSV‐mediated hypomethylation from lowly invasive to highly invasive stages (Table , Figure A). One of the highest changes was identified within a promoter region of SEMA3A , a gene with reported tumor suppressor functions (Table , Figure B) . Publicly available clinical data show methylation of the studied CpG locus within SEMA3A and gene downregulation in tumors versus normal tissue.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation